Emerging Biomedical Applications of Enzyme-Like Catalytic Nanomaterials. Issue 1 (January 2018) - Cormode, David P.; Gao, Lizeng; Koo, Hyun
Abstract : Nanomaterials have been developed for many biomedical applications, including medical imaging, drug delivery, and antimicrobial coatings. Intriguingly, nanoparticles can display 'enzyme-like' activity and have been explored as alternatives to natural enzymes in several industrial and energy-related applications. Recently, these catalytic nanomaterials with enzyme-mimetic properties have found new biomedical applications, from biofilm disruption to protection against neurodegeneration and tumor prevention. In this review we focus on recent in vivo studies demonstrating potential therapeutic uses of catalytic nanomaterials. We also provide insights about the relationships between catalytic activity, therapeutic efficacy, and biocompatibility that are critical for clinical translatability. Finally, we discuss current challenges and future directions for the use of these nanomaterials as novel platforms for the development of sustainable, affordable, and safe therapeutics. Trends: In the field of nanozymes, in vivo explorations of their effectiveness as therapies for many types of disease, such as biofilm infections, stroke, myocardial ischemia, cancer, hyperuricemia, and neurodegeneration, are on the rise. Translational issues such as clearance, metabolism, degradability, biocompatibility, and side effects are being assessed, as nanoparticles have the potential for long-term retention in organs such as the liver and spleen. Nanozymes are starting to be designed to have specificity of function or stimulus-triggered activity (some nanoparticles can exhibit specific enzymatic activity depending on their microenvironment). There is a trend towards the use of iron oxide-based nanozymes for in vivo studies, since several iron oxide nanoparticles have been approved by the FDA for clinical use, such as MRI contrast agents and iron replacement therapy.